Assessment of knowledge and practice of dentists towards Coronavirus Disease (COVID-19): a cross-sectional survey from Lebanon - Zeina Nasser; Youssef Fares; Rama Daoud; Linda Abou-Abbas (BMC, 2020)
Abstract Background Coronavirus Disease (COVID-19) epidemic is a public health emergency of international concern. Dentists are exposed to the enormous risk of COVID-19 infection during this epidemic. This study aims to assess the knowledge and practice of dentists toward the COVID-19 epidemic in Lebanon. Methods We conducted an online survey using the snowball-sampling technique. Information on socio-demographic data, knowledge, practice, and additional information required concerning COVID-19 were collected. Results Our results showed that the majority of the Lebanese dentists had good knowledge (91.3%), and nearly half of the respondents had a good practice (58.7%) regarding COVID-19. The most common information source was the World Health Organization (73.7%). Multiple linear regression showed that specialist dentists who completed training on COVID-19 with a high level of knowledge had better practice. Conclusions Lebanese dentists revealed good knowledge regarding COVID-19. However, dentists had limited comprehension of the extra precautionary measures that protect the dental staff and patients from this virus. Our findings have important implications for the development of strategies suitable for improving the level of practice among dentists and enhance prevention programs.